Examination of Therapeutic Potential of Luteolin on Acute Lymphoblastic Leukemia Cells and Changes in Macromolecules - Baran, Yusuf; Çetinkaya, Melisa (01. Izmir Institute of Technology, 2023)
Acute lymphoblastic leukemia (ALL) is a genetic disease that arises from the various recurrent genetic alterations blocking the differentiation of the precursor B-and T-cells, resulting in the aberrant proliferation and survival of immature lymphoblasts within the peripheral blood and bone marrow. T-ALL is an aggressive type of ALL, and the current treatment strategies, including the high-intensity combination chemotherapy, result in different side effects which are difficult to accept or ultimately lead to the death of patients as substantial toxicity of those chemotherapeutics is known to healthy cells alongside with the cancer cells. Therefore, there is a need to identify nontoxic, costeffective, potent, and readily available treatment options for T-ALL patients. One alternative option is the flavonoids in cancer therapeutics, which are secondary metabolites of plants mainly responsible for plants' colors and flower aromas. Luteolin is an extensively researched member of the flavonoids with anticancer properties shown in various cancer types, except for the T-ALL. This study demonstrated Luteolin's time- and dose-dependent antiproliferative, cytostatic, and apoptotic effects on T-ALL cells for the first time in the literature. Also, the macromolecular changes caused in response to Luteolin treatment in T-ALL cells were examined for the first time. As a consequence, it was found that Luteolin had antiproliferative, apoptotic, and cytostatic effects on T-ALL cells, suggesting its therapeutic potential and was demonstrated to cause an increase in the lipid-to-protein ratio and the hydrocarbon chain length of the lipid acyl chains in a dose-dependent manner on T-ALL cells.

Akut lenfoblastik lösemi (ALL) genetik bir hastalık olup öncül B ve T hücrelerinin farklılaşmasını bloke eden çeşitli tekrarlayan genetik değişikliklerden kaynaklanır ve olgunlaşamamış lenfoblastların anormal çoğalması ve hayatta kalmasıyla ve kan iliği, periferik kan gibi bölgelerde birikimi ile sonuçlanır. T-ALL, ALL'nin agresif bir türüdür ve mevcut tedavi stratejileri arasında kullanılan kombinasyon kemoterapisi, hastalarda ölüme yol açan veya kabul edilmesi zor olan yan etkilere sebep olmaktadır. Bunun nedenlerinden biri de kemoterapötiklerin kanser hücreleri yanı sıra sağlıklı hücrelere de önemli düzeyde toksisiteye sebep olmasıdır. Bu nedenle, T-ALL hastaları için toksik olmayan, maliyeti uygun, etkili ve kolayca bulunabilen tedavi seçeneklerinin geliştirilmesine acil bir ihtiyaç vardır. Kanser için alternatif terapötik ajan olarak son yıllarda bitkilerin ikincil metabolitleri olan flavonoidlerin kullanımının, esas olarak bitkilere renk ve aroma vermekle sorumludurlar, araştırmaları önem kazanmıştır. Luteolin, T-ALL hariç diğer kanser çeşitlerinde antikanser özelliği kapsamlı bir şekilde gösterilmiş olan bir flavonoiddir. Bu çalışma ile, literatürde ilk kez Luteolin'in T-ALL hücreleri üzerindeki doza ve zamana bağlı antiproliferatif, apoptotik ve sitostatik etkileri gösterilmiştir. Ayrıca, yine literatürde ilk defa Luteolin tedavisine yanıt olarak T-ALL hücrelerinde oluşan makromoleküler değişiklikler incelenmiştir. Sonuç olarak, Luteolin'in T-ALL hücreleri üzerinde antiproliferatif, apoptotik ve sitostatik etkilere sahip olduğu bulunmuş olup, bu da Luteolin'in T-ALL için terapötik potansiyelini işaret etmektedir. Aynı zamanda, Luteolin'in T-ALL hücrelerinde doza bağlı olarak lipid-protein oranında ve lipidlerin asil zincirlerindeki hidrokarbon zincir uzunluğunda artışa sebep olduğu gösterilmiştir.
Luteolın'in Akut Lenfoblastik Lösemi Hücreleri Üzerindeki Terapötik Potansiyelinin ve Makromoleküler Etkilerinin İncelenmesi
Thesis (Master)--İzmir Institute of Technology, Molekular Biology and Genetics, Izmir, 2023
Includes bibliographical references (leaves. 65-95)
Text in English; Abstract: Turkish and English
Keywords: Acute lymphoblastic leukemia; T-ALL cells; Luteolin; Macromolecules